Pengaruh Layout Dan Variasi Produk Terhadap Keputusan Pembelian Melalui Daya Tarik Produk: (Survei Pada Konsumen Baso Assyukur Tasikmalaya) - Elin Herlina (CV. ULIL ALBAB CORP, 2022)
This study aims to determine the effect of layout and product variation on purchas decisions through product attrativeness Baso Assyukur Tasikmalaya. The method used in this study is a survey method with a causal research design. The population in this study unknow and the sample is takenas many as 100 responden. The analytical tool used is pat analysis. The result showed rhat layout had a significan effect on the attrativeness of Baso Assyukur Tasikmlaya product. Prouct variations have a significant effect on the attrativeness off Baso Assyukur Tasikmalaya Product. Layout has a significant effect on purchasing decision through the attrativeness of baso Assyukur Tasikmalaya product. Produk variations have a significant effect on purchasing decision through the attrativeness off baso assyukur Tasikmalaya product.